Semantics Tammam Ḥassan On Waqf Lazim Verses In Surah Al-Ma’idaṯ - Mursyid Rosd; Azhar Muhammad; Amirul Haqeem Bin Abd Ghani; Muhammad Abrar Bahaman; Faizul Nizar Anuar; Safiyyah Ahmad Sabridoi.org.; Khairunneezam Mohd Noor (Tuijin jishu, 2024)
Tuijin Jishu/Journal of Propulsion Technology Volume 44 No.5 Page (885-897)